The ethnic business in Colombia: the case of Venezuelan entrepreneurs in Bucaramanga (2021)
The number of migrants from Venezuela in Colombia has increased substantially. Due to its geographical location with an extended border, Bucaramanga has been one of the main cities receiving this migratory flow. This article characterizes the business initiatives developed by Venezuelan migrants in Bucaramanga between 2010 and 2018, through three dimensions of analysis: sociodemographic, business background and business performance in Colombia. To this end, 19 surveys and observation visits were carried out. It is concluded that in Bucaramanga there is an "ethnic economy", understood as a set of businesses created by migrants to face the barriers of access to the labor market and xenophobia, but the criticisms that have been formulated about this concept are ratified, since there is no evidence of a close relationship between owners and migrant clients, but in the criterion of work teams that support the productive process.